Computer-managed maintenance systems in process plants a step-by-step guide to effective management of maintenance, labor, and inventory in your operation - Cato, William W. (Gulf Pub. Co., 1999)
CMMS is an integrated set of computer programs and data files used to efficiently govern the massive amounts of data generated by maintenance, inventory control, and purchasing. With a CMMS in place, you will effectively manage both the human and capital resources in your plant. Now you can: trace materials used and track their costs; maintain optimum, cost-effective inventory levels; better utilize labor; automatically create maintenance histories; and make maintenance cost data readily accessible in a variety of formats.